KETERAMPILAN LITERASI INFORMASI MAHASISWA MENURUT STANDAR KOMPETENSI LITERASI INFORMASI ASSOCIATION OF COLLEGE & RESEARCH LIBRARIES (ACRL) - Prasetyo, Djoko; Rahman Rosyidi, Fathu; Rohmadi, Rohmadi; Auliyani, Uswatun; Handayani, Sri (BACA: Jurnal Dokumentasi dan Informasi, 2018)
The research on the analisis of information literacy skills of undergraduate students of Universitas Jenderal Soedirman by using standards of information literacy competency ACRL has been conducted. It is aimed to know the literacy skill of undergraduate students of bacth 2014 and 2015. The skills include determination of the nature and scope of the required information; ability of access the information needed effectively and efficiently; evaluation of information and sources critically; capability of using the information to accomplish particular purposes; and understanding of economic, legal, and social aspects which are related to the use of information. This is a descriptive research with samples of undergraduate students of Unsoed as many as 334 students among 7,376 students. Thus, one variable analysis is used in order to see the value of the central tendency and then tested by using the rate value. The results showed that students’ information literacy skills measuring by the standard information literacy competency standards for higher education from ACRL are in the skilled category. Some standards need to be improved, e.g., the competency standard in determination of the nature and scope of the information which has the lowest score of 3,73. The others, the standard of competence to access information effectively and efficiently, with an average score of 3,88 as well as the competence standard to evaluate the information and its sources, with an average score of 3,84 are also need to be improved.